An unusual journey through post-war residential architecture - Tavares, Maria Fernanda Gaspar, 1970- (2021)
In September and October 1958, Nuno Teotonio Pereira and Nuno Portas embarked on a trip through Europe with the aim of coming into contact with different experiences in the area of housing. Spain and Italy were the recipients of short visits that sought to understand the social and economic structure in the post-World War II period and the responses of the various bodies responsible for the housing sector. In a decade marked by new paths being taken by architects committed to a process of social transformation, these two Portuguese architects, faced with the housing deficit that was making itself felt in Portugal, brought back from this journey a number of modern references that inevitably were transformed into a kind of script to be put into practice, though also with an inevitable critical (re)vision. In Portugal, so-called low-cost housing (HE or Habitações Económicas) had been using monies from the Federation of Social Security Funds to build “low-income housing” since 1947. In Italy, the main objective of the INA-Casa programme, which commenced in 1949, was to combat unemployment through construction. Of interest here is not just the more operational side of the cases, but also to understand how low-cost housing, through the teachings of the aforementioned duo of architects, came to methodologically apply the principles of the Italian body, mainly by means of the similar impulses coming from a new generation that was motivated to experiment with renewed architecture that remained close to and was easily understood by the popular classes.